Biometrics and germination of Macrolobium acaciifolium (Benth.) Benth. seeds from floodplain and igapó in Central Amazonia - Santos, Lucélia Rodrigues; Almeida, Marilene de Campos; Wittmann, Florian Karl (Iheringia - Serie Botanica, 2020)
This study focuses on the morphometric analysis of seeds of Macrolobium acaciifolium from environments of Amazonian floodplains and igapó, as well as the effect of the substrates of these areas on the germination and seedling formation of the species. A biometric analysis of 200 M. acaciifolium seeds from populations of both Central Amazon environments was performed. In greenhouse, germination of seeds under their soil of origin and under vermiculite was analyzed. The seeds from igapó presented higher mean weight and thickness compared to the floodplain seeds, which, on occasion, presented higher averages of length and width. The seed germination percentage of both environments was similar, but the speed was higher for the igapó seeds, regardless of the substrate. The igapó seeds are larger than the floodplain seeds and, because they have more reserves, they are able to produce more vigorous seedlings, regardless the physical conditions of the substrate. © 2020 Fundacao Zoobotanica do Rio Grande do Sul. All rights reserved.
Biometria e germinação de sementes de Macrolobium acaciifolium (Benth.) Benth. de várzea e igapó da Amazônia Central
Keywords: Biomass; Flooded forests; Propagation of forest species